Anti-tubulin drugs conjugated to anti-ErbB antibodies selectively radiosensitize - Stephen R. Adams (Nature Portfolio, 2016)
Drugs that sensitize tumour cells to ionizing radiation are prized because they can overcome resistance to radiotherapy. Here, the authors show that anti-tubulin drugs conjugated to cetuximab or trastuzumab can radiosensitize EGFR- or HER2-expressing tumors by increasing DNA damage and cell death due to ionizing radiation.